2007
DOI: 10.1161/circulationaha.107.706986
|View full text |Cite
|
Sign up to set email alerts
|

CC Chemokine Ligand-5 (CCL5/RANTES) and CC Chemokine Ligand-18 (CCL18/PARC) Are Specific Markers of Refractory Unstable Angina Pectoris and Are Transiently Raised During Severe Ischemic Symptoms

Abstract: Background-Chemokines play an important role in atherogenesis and in ischemic injury and repair; however, prospective data on individual chemokines in unstable angina pectoris (UAP) are scarce. Therefore, we assessed chemokine patterns in a prospective cohort of patients with UAP. Methods and Results-Plasma samples of 54 patients with Braunwald class IIIB UAP were examined at baseline for 11 chemokines and 5 inflammatory mediators via multiplex analysis. Levels of CC chemokine ligand (CCL)-5 (also known as RAN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(96 citation statements)
references
References 43 publications
6
90
0
Order By: Relevance
“…With regard to RANTES, in our study there are clear species differences in the RANTES pattern between postmenopausal women and ovariectomized rats. In this context, the circulating RANTES levels in humans are higher than those in rodents (nanogram range vs picogram range) (29,30). Additionally, since it is now well known that platelets store RANTES in their ␣-granules and release it during acute stages of inflammation (31)(32)(33), it is also possible that the number of circulating platelets or the amount of RANTES stored in them differs between humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to RANTES, in our study there are clear species differences in the RANTES pattern between postmenopausal women and ovariectomized rats. In this context, the circulating RANTES levels in humans are higher than those in rodents (nanogram range vs picogram range) (29,30). Additionally, since it is now well known that platelets store RANTES in their ␣-granules and release it during acute stages of inflammation (31)(32)(33), it is also possible that the number of circulating platelets or the amount of RANTES stored in them differs between humans and rats.…”
Section: Discussionmentioning
confidence: 99%
“…In concurrence with our results, Bae et al (67) have recently reported that RANTES is regulated in a NADPH oxidase-dependent manner. Furthermore, a transient increase in RANTES levels was reported in patients experiencing unstable angina pectoris (68). TNF-␣ plays a key role in the inflammatory cascade associated with atherosclerosis (69) and several studies support the association of increased TNF-␣ levels with increased risk of myocardial infarction (70,71).…”
Section: That Cd44mentioning
confidence: 97%
“…IL-1β increases dynamically following CME and is associated with impaired cardiac function [37] . RANTES has been identified as a specific marker for unstable angina pectoris by several studies [38][39] . The adhesion molecule, ICAM-1, also represents a marker of slow coronary flow caused by microvascular dysfunction [40][41] .…”
Section: Wwwchinapharcom Zhang Y Et Almentioning
confidence: 99%